Substrate-induced microstructure effects on the dynamics of the photo-induced metal–insulator transition in VO2 thin films. (14th January 2015) - Radue, E; Wang, L; Kittiwatanakul, S; Lu, J; Wolf, S A; Rossi, E; Lukaszew, R A; Novikova, I
Abstract: We investigate the differences in the dynamics of the ultrafast photo-induced metal–insulator transition (MIT) of two VO2 thin films deposited on different substrates, TiO2 and Al2 O3, and in particular the temperature dependence of the threshold laser fluence values required to induce various MIT stages in a wide range of sample temperatures 150–320 K. We identified that, although the general pattern of MIT evolution was similar for the two samples, there were several differences. Most notably, the threshold values of laser fluence required to reach the transition to a fully metallic phase in the VO2 film on the TiO2 substrate were nearly constant in the range of temperatures considered, whereas the VO2 /Al2 O3 sample showed clear temperature dependence. Our analysis qualitatively connects such behavior to the structural differences in the two VO2 films.